The validity and reliability of the Malaysian osteoporosis knowledge Tool in postmenopausal women - Lai, P.S.; Chua, S.S.; Chan, S.P.; Low, W.Y. (2008)
OBJECTIVES: To design a valid and reliable questionnaire, the Malaysian Osteoporosis Knowledge Tool (MOKT), to assess the knowledge of postmenopausal osteoporotic women in Malaysia, on osteoporosis and its treatment. METHODS: A 40-item instrument was designed and tested in this study. The scores ranged from 1 to 40, which were then converted into percentage. This was administered to 88 postmenopausal osteoporotic women who were taking alendronate (patient group) and 43 pharmacists (professional group). The MOKT was administered again to the patient group after 1 month. RESULTS: Flesch reading ease was 57, which is satisfactory, while the mean difficulty factor+/-S.D. was 0.73+/-0.25, indicating that the MOKT is moderately easy. Internal consistency of the instrument was good with Cronbach's alpha=0.82. The test and retest scores showed no significant difference for 38 out of the 40 items, indicating that the questionnaire has achieved a stable reliability. Level of knowledge on osteoporosis and its treatment was good with a mean score+/-S.D. of 69.0+/-13.9 and 81.6+/-9.5 in the patient and professional group, respectively. The difference in knowledge scores between the two groups was statistically significant (p<0.001). CONCLUSIONS: In conclusion, the 40-item questionnaire (MOKT) is a reliable and valid instrument for measuring knowledge on osteoporosis in the Malaysian setting. Therefore, it can be used to identify individuals in need of educational interventions and to assess the effectiveness of education efforts as part of osteoporosis management.